Comparative morphological and anatomical analysis of the feverfew herb varieties Phlora Pleno and White Gem - K. R. Hordiei; T. M. Gontova; S. P. Mashkovska (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Feverfew (Tanacetum parthenium (L.) Schultz Bip. is a perennial plant of the Aster family, which has an anti-migraine, anti-inflammatory and analgesic activity. These days studying of the feverfew varieties is actual in order to expand the raw material base because species and varieties are known to have a similar chemical composition. In Ukraine, the varieties White Gem and Phlora Pleno are widely cultivated and they are unpretentious to the natural and climatic conditions of Ukraine. The morphological and anatomical study of the selected varieties previously has not been studied, therefore this analysis is actual. The aim of the work was to conduct a morphological and anatomical analysis of the feverfew herb varieties Phlora Pleno and White Gem. The object of the study was samples of the feverfew herb varieties Phlora Pleno and White Gem collected during the period of mass flowering in 2018-2019 on experimental plots of the Botanical Garden of the National University of Pharmacy (Kharkiv, Ukraine) and the National Botanical Garden N. N. Grishka (Kiev, Ukraine.). Morphological features were examined on fresh, dry and fixed raw materials using a Levenhuk Zeno Handy ZH19 magnifier. Anatomical studies were carried out using raw materials fixed in a mixture of alcohol-glycerin-water (1:1:1) and in accordance with the requirements of the SPhU. As a result of the analysis the general and individual morphological and anatomical features of the feverfew herb varieties White Gem and Phlora Pleno were determined. The individual morphological features of the Phlora Pleno variety include white, female ray flowers up to 1.0 cm long, arranged in 2-3 rows; variety White Gem - white, female up to 0.8 cm long, located singly ray flowers. The individual anatomical features of the Phlora Pleno variety include the paracytic and anisocytic types of the stomata; single prismatic crystals and druses in the mesophyll; variety White Gem - anomocytic type of the stomata, on the epidermis of the stem - trichomes with a lobed terminal cell and glandules. For the first time a comparative morphological and anatomical analysis of the feverfew herb varieties Phlora Pleno and White Gem collected in Ukraine was carried out. The general and distinctive features of each variety, as well as their main diagnostic features, have been determined, therefore it will be used later to standardize the feverfew herb varieties Phlora Pleno and White Gem.